Análise paleoecológica e paleoparasitológica em coprólitos de vertebrados do quaternário do sítio paleontológico e arqueológico lagoa Uri de Cima (região de Salgueiro, Pernambuco, Brasil) - Nascimento, Carolina Santa Isabel (2017)
Paleoparasitology is the study of recovered parasites from human and no human animals remains. One of the main focuses of the Paleoparasitolgy are coprolites, from which various parasitic structures can be recovered. In this work 24 coprolites from different zoological origins were observed by optical microscopy. They were donated by the Laboratório de Paleoparasitologia of the Escola Nacional de Saúde Pública (ENSP)/Fiocruz in a partnership with the Laboratório de Paleoecologia e Paleoicnologia (LPP), Universidade Federal de São Carlos. The samples come from the paleontological and archaeological site Lagoa Uri de Cima, located in the region of Salgueiro, State of Pernambuco (Brazil), in semi-arid region in the Brazilian Northeast. Although necrobioma formed by fungi was found in 45.83% of the samples and by mites in 8.33% of them, it was still possible to recover items such as diet remnants and parasitic structures, as well as sponge spicules, diatom and other biological items. In the paleoparasitological analysis, main objective of the work, two of the samples were positive for gastrointestinal parasites. The sample A2726 (8,800 ± 1320 years BP) presented Cestoda eggs, similar to Diphyllobothrium sp., and A2712 (4,600 ± 900 years BP) presented one Nematoda larvae and 260 Eimeria sp. oocysts, possibly a new species of this genus. The presence of only one species, but with more than one morphotype, was suggested by a graphical analysis, unprecedented for this purpose, visualized with the software Gephi v. 0.9.1. The positive results for parasitology support the zoological origin of the coprolites and indicating that the animal populations of the Pleistocene/Holocene that lived in the surroundings of the Uri de Cima were affected by parasitoses. The relationship between necrobioma and organic matter present in the fecal matters, the taphonomic agents that may alter the initial characteristics of the material and the possible implications in the parasite relations in situations of loss of hosts and reservoirs due to extinctions are also discussed here.